2018
DOI: 10.4236/oalib.1104371
|View full text |Cite
|
Sign up to set email alerts
|

A Trend Analysis of Temperature in Selected Stations in Nigeria Using Three Different Approaches

Abstract: This study used daily observation data obtained from the Nigerian Meteorological Agency (NiMet) to investigate the temperature trend of Nigeria from 1981-2015. The data were homogenised using the Quantile Matching (QM) method and Quality Controlled. The data have been transformed into three sets of data with different periods: daily, monthly and yearly. The datasets (daily, monthly and yearly) were checked for autocorrelation and if they were found auto correlated, the Modified Mann Kendall (MMK) and the PreWh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 40 publications
1
7
0
1
Order By: Relevance
“…Similarly, other studies (Ragatoa et al 2018;Eresanya et al 2018;Amadi et al 2014) have shown a rising trend in air temperature across Nigeria.…”
Section: Trend Analysis Of Atmospheric Temperaturesupporting
confidence: 51%
“…Similarly, other studies (Ragatoa et al 2018;Eresanya et al 2018;Amadi et al 2014) have shown a rising trend in air temperature across Nigeria.…”
Section: Trend Analysis Of Atmospheric Temperaturesupporting
confidence: 51%
“…Mann-Kendall (MK) and four modified Mann-Kendall methods (MMK) were applied to examine the trends. Previous studies showed better performance of the MMK method with the monthly data [169]. The results of the MK and MKK tests applied to the NDVI data series at a confidence interval of 90% are shown in Table 9.…”
Section: Spatiotemporal Analyses Of Trend Using Landsat Ndvi Time Seriesmentioning
confidence: 90%
“…Wavelet analysis (Abdullayev et al, 2017;Joseph et al, 2015;Banović et al, 2013), as the name suggests, is a small waveform. The so-called "small" or "let" means that it has attenuation; the so-called "wave" refers to its volatility, and its X. T. Tian et al Mann-Kendall is also often used for the detection of precipitation and drought frequency trends under the influence of climate change (Bera, 2017;Ragatoa et al, 2018;Koudahe et al, 2017).…”
Section: Methodsmentioning
confidence: 99%